2018
DOI: 10.1126/scitranslmed.aam7019
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile uses amino acids associated with gut microbial dysbiosis in a subset of patients with diarrhea

Abstract: The gut microbiota plays a critical role in pathogen defense. Studies using antibiotic-treated mice reveal mechanisms that increase susceptibility to Clostridioides difficile infection (CDI), but risk factors associated with CDI in humans extend beyond antibiotic use. Here, we studied the dysbiotic gut microbiota of a subset of patients with diarrhea and modeled the gut microbiota of these patients by fecal transplantation into germ-free mice. When challenged with C. difficile, the germ-free mice transplanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
156
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(168 citation statements)
references
References 65 publications
10
156
2
Order By: Relevance
“…A high-fat diet was also observed to intensify CDI in a hamster model of infection (31); however, to our knowledge, a high-fat/high-protein diet has never been explored in animal models of CDI, as typical diets used for mouse and hamster models of CDI have Յ10% kcal from fat and Յ30% kcal from protein. The poor CDI outcome observed here for mice fed the high-fat/highprotein diet compared with the high-fat/low-protein diet is consistent with known relationships between dietary protein and CDI in both laboratory mice with native murine microbiota (13) and humanized mice fed a defined amino acid diet deficient in the Stickland electron acceptor proline (11). The major diets used in these other studies used relatively low (Յ20%) concentrations of protein provided as casein.…”
Section: Discussionsupporting
confidence: 83%
“…A high-fat diet was also observed to intensify CDI in a hamster model of infection (31); however, to our knowledge, a high-fat/high-protein diet has never been explored in animal models of CDI, as typical diets used for mouse and hamster models of CDI have Յ10% kcal from fat and Յ30% kcal from protein. The poor CDI outcome observed here for mice fed the high-fat/highprotein diet compared with the high-fat/low-protein diet is consistent with known relationships between dietary protein and CDI in both laboratory mice with native murine microbiota (13) and humanized mice fed a defined amino acid diet deficient in the Stickland electron acceptor proline (11). The major diets used in these other studies used relatively low (Յ20%) concentrations of protein provided as casein.…”
Section: Discussionsupporting
confidence: 83%
“…A growing body of evidence points to dietary intervention as a promising new approach to prevent CDI colonization (4, 15) . One recent study showed that a diet poor in proline (an essential amino acid for C. difficile growth) prevented C. difficile carriage (4) . Another study demonstrated that mice fed a diet deficient in MACs (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While dietary fiber content can result in microbial metabolites that are protective against CDI, other diet-influenced metabolites seem to promote the pathogenesis of CDI. For instance, consistent with C. difficile being auxotrophic for the amino acid proline, experiments conducted in gnotobiotic mice have supported that mice were protected from C. difficile colonization with low-proline diets (4) .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the reductive branch, glycine and/or proline are reduced by the selenium-containing glycine and proline reductases to acetate or 5-aminovalerate, respectively, to regenerate the NAD+ pool (Bouillaut et al, 2015). Proline is a highly relevant amino acid for C. difficile growth and a recent study by Battaglioli et al (Battaglioli et al, 2018) found that the proline reductase is required for a robust infection in gnotobiotic mice colonized with a dysbiotic patient microbiota that is susceptible to CDI. These findings combined indicate that proline metabolism by C. difficile impacts multiple facets of the C. difficile lifestyle – from colonization and growth to the production of toxic molecules to potentiate a C. difficile growth advantage (Bouillaut et al, 2015; Kang et al, 2018).…”
mentioning
confidence: 99%